A Giant Case of Pyonephrosis Resulting from Nephrolithiasis - Ali Erol; Soner Çoban; Ali Tekin (Case Reports in Urology)
Pyonephrosis is an uncommon disease that is associated with suppurative destruction of the renal parenchyma in adults. Upper urinary tract infection and obstruction play a role in its etiology. Immunosuppression from medications (steroids), diseases (diabetes mellitus, AIDS), and anatomic variations (pelvic kidney, horseshoe kidney) may also be risk factors for pyonephrosis. Fever, shivering, and flank pain are frequent clinical symptoms. On physical examination, a palpable abdominal mass may be associated with the hydronephrotic kidney. Septic shock and death can occur if the disorder is not treated with urgent surgery. After the acute phase, most patients are treated with nephrectomy. In this paper, we share the etiology, clinical features, diagnosis and treatment of pyonephrosis using the background of a case with giant pyonephrosis developing due to a kidney stone, the most common cause of upper urinary tract obstruction.